Out-of-Pocket Expenditure (OOPE) on Selected Surgeries in the Obstetrics and Gynaecology Department incurred by Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY), Private Health Insurance and Uninsured Patients in a Tertiary Care Teaching Hospital in Karnataka state of India. [version 2; peer review: 2 approved] - Dr. Kumar Sumit; Reena Verma; Prajwal Salins; Helmut Brand; Siddhartha Sankar Acharya; Sagarika Kamath; rajesh kamath; Dr. Vidya Prabhu (F1000Research)
Introduction OOPE for healthcare services is a major concern within the Indian healthcare system. 30% of the population remains uninsured despite increasing health insurance coverage. For obstetrics and gynaecology (OBG) patients financial obstacles like OOPE can delay access to health care, evaluating spending patterns can inform policies to enhance accessibility, affordability and equitable health. Methodology A retrospective study was conducted at a tertiary care teaching hospital in Karnataka state of India to analyze OOPE for 905 OBG patients who underwent Cesarean Section(C-Section), Laparoscopic Hysterectomy, Laparoscopic Cystectomy, Laparoscopic Myomectomy and Laparoscopic Assisted Vaginal Hysterectomy (LAVH). These were the top five most performed obstetrics and gynecology surgeries in the tertiary care teaching hospital between January 2023 and July 2023. Data was collected across AB-PMJAY, private health insurance, uninsured patients and analyzed using descriptive statistics (mean, median) and the Shapiro-Wilk test for data normality. Results The study analyzed OOPE across 905 OBG patients. Findings show AB-PMJAY provided full coverage with zero OOPE for all surgeries. Though private health insurance reduced OOPE compared to uninsured patients under private health insurance still faced significant financial burden. Variations existed in minimum and maximum OOPE and percentage of OOPE across different private insurances. All the uninsured patients incurred 100% OOPE, with a median OOPE of Rs. 33,257 (405.67 USD) to Rs. 57,053 (695.76 USD) and a mean OOPE of Rs. 39,848 (485.95 USD) to Rs. 60,687 (740 USD) across the surgeries. Discussion Findings of the study show that AB-PMJAY is highly effective in reducing OOPE and enhancing financial risk protection for OBG patients. Patients covered by private health insurance incurred less OOPE, yet the burden remained considerable. High OOPE rates for uninsured patients (100%) and private health insurance (38.15%) compared to 0% OOPE in AB-PMJAY emphasizes the need for the continued expansion of AB-PMJAY.